2003
DOI: 10.1101/gr.808603
|View full text |Cite
|
Sign up to set email alerts
|

The Organization and Rate of Evolution of Wheat Genomes Are Correlated With Recombination Rates Along Chromosome Arms

Abstract: Genes detected by wheat expressed sequence tags (ESTs) were mapped into chromosome bins delineated by breakpoints of 159 overlapping deletions. These data were used to assess the organizational and evolutionary aspects of wheat genomes. Relative gene density and recombination rate increased with the relative distance of a bin from the centromere. Single-gene loci present once in the wheat genomes were found predominantly in the proximal, low-recombination regions, while multigene loci tended to be more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
214
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 297 publications
(238 citation statements)
references
References 62 publications
21
214
3
Order By: Relevance
“…hordei diverged 6.3 (± 1.1) million years ago (Supplementary Note). This finding narrows down previous estimates, which ranged from 4.7 to 10 million years ago 5,17 , and indicates that the two formae speciales diverged several million years ago, after the divergence of their hosts 10-15 million years ago 18,19 . As in a previous study 17 , we found gene order to be largely conserved between B. graminis f.sp.…”
Section: E T T E R Scontrasting
confidence: 54%
“…hordei diverged 6.3 (± 1.1) million years ago (Supplementary Note). This finding narrows down previous estimates, which ranged from 4.7 to 10 million years ago 5,17 , and indicates that the two formae speciales diverged several million years ago, after the divergence of their hosts 10-15 million years ago 18,19 . As in a previous study 17 , we found gene order to be largely conserved between B. graminis f.sp.…”
Section: E T T E R Scontrasting
confidence: 54%
“…This is consistent with a strong negative correlation between repetitive DNA content and the recombinational length of rice chromosomes and with the much greater abundance of repetitive DNA than genes in the pericentromeric regions . Accelerated gene loss in recombinationpoor regions of wheat (Akhunov et al, 2003) and a propensity for small insertions in centromeric regions of mammalian genomes (Bailey et al, 2001) lend further support to this idea.…”
Section: Euchromatin Versus Heterochromatin: Tales Of Two Genomessupporting
confidence: 48%
“…Colinearity in the order of loci in the wheat genomes is largely conserved except for a 4A-5A-7B translocation, a putative 2B-6B translocation, and two inversions on chromosome 4A (Hossain et al 2004a;Peng et al 2004). Gene density in wheat tends to increase with relative distance from the centromere, with some of the highest densities observed in several distal regions of the chromosomes (Akhunov et al 2003;Erayman et al 2004). However, the overall relationship between gene density and relative position on the chromosome is weak (Akhunov et al 2003).…”
mentioning
confidence: 97%